Pengaruh Fasilitas Belajar di Rumah dan Gaya Belajar Terhadap Prestasi Belajar Siswa Kelas X Pemasaran Pada Mata Pelajaran Komunikasi Bisnis SMK Negeri 2 Padang - Nessy Gresita Dwi H; Armida S (Universitas Negeri Padang, 2021)
The study was conducted to: (1) The Effect of Home Study Facilities on Student Achievement (In class X Marketing on Business Communication Subjects at SMK Negeri 2 Padang) (2) The Effect of Learning Styles on Student Achievement (In class x Marketing on Eyes) (2). Business Communication Lessons at SMK Negeri 2 Padang). (3) The Effect of Home Learning Facilities and Learning Styles on Student Achievement. The study using a data processing program using SPSS version 23. The population these were students of class X Marketing at SMK Negeri 2 Padang which consisted of 106 students, the sample of this study used 84 students. The analysis included normality test, multicollinearity test and heteroscedasticity test. Hypothesis is multiple regression analysis, F test, coefficient of determination and t tes. The results is: (1) There is a positive and significant effect of Home Study Facilities on Student Achievement (In Class X Marketing in Business Communication Subjects at SMK Negeri 2 Padang). (2) There is a positive and significant effect of learning styles on student achievement. (3) There is a positive and significant effect of Home Study Facilities and Learning Styles on Student Achievement (In Class X Marketing Subjects at SMK Negeri 2 PadangKeywords : home study facilities, learning style, learning achievement